KONTRIBUSI PESANTREN PERSATUAN ISLAM BAGI PENGUATAN PENDIDIKAN ISLAM DI INDONESIA - Toto Suharto (Millah: Journal of Religious Studies, 2011)
The Pesantren Persatuan Islam that formed in 1936, is one of the private educational institutions in Indonesia. Until 1999, this institution has 154 educational institutions spread all over Indonesia. Although the current views of Islamic politics in Indonesia Persatuan Islam is not the mainstream, because he was small and not strong, but its contribution to Islam in Indonesia should also be taken into account. The internal contributions of Pesantren Persatuan Islam can be seen from the aspect of indoctrination, that this institution is an event-style formulation of the Persatuan Islam religious understanding. Then externally, the contribution of Pesantren Persatuan Islam can be viewed in terms of institutions, namely the institutional system, called pesantren. Unlike boarding institution in the traditional understanding, for the Pesantren Persatuan Islam are synonymous with modernity, that is still oriented “boarding-centric”, but with adaptive and accommodative attitude towards the development of science and technology originating from the West. With such institutional concept, Pesantren Persatuan Islam successfully gave birth to thousands of Muslim volunteers who spread to all parts of Indonesia. Number of Pesantren Persatuan Islam spread over almost the whole of Indonesia was already assured a large contribution to the strengthening of Islamic education in Indonesia.